Public Opinion and Public Opinion Polls: Views of Slovenian Journalists and Politicians - Slaček Brlek, Sašo (Javnost-The Public, 2009)
The article analyses the institutional embededdnes of public opinion polling in the political system and the system of mass media and the implications of the institutionalization of public opinion in the form of public opinion polls for the conceptualization of public opinion. In-depth Interviews with editors and journalists of three Slovenian dailies (Delo, Dnevnik and Večer) and a survey of Slovene politicians and journalists are used to illuminate subjective responses to the institutional logic of polling. It is argued that the equalisation of poll results with public opinion is theoretically untenable and even undemocratic, but that the instrument of polling is not inherently undemocratic. The analysis of the institutional embeddedness of polling and subjective responses to it suggest that other, more democratic, uses of polling are possible, which are contingent upon dissolving the equation mark between public opinion and poll results.